Laboratory evaluation of short and long term performance of hot-poured sealants. (1st September 2017) - Li, Feng; Zhou, Siqi; Cai, Wenyuan; Du, Yuchuan; Li, Li
Highlights: Four tests were used to evaluate the short term performance of sealants. Two tests were used to evaluate the thermal and immersion stability of sealants. An evaluation system of short and long term performance was presented. Abstract: Hot-poured sealants are commonly applied to repair cracks on asphalt pavements. However, existing methods of performance evaluation do not fully reflect the performance of hot-poured sealant for pavement application. Therefore, this article proposes different tests, melting point and melt flow index of packing films, sealant viscosity, segregation, thermal aging performance, and bond after water immersion, to specifically address identified problems and evaluate the short and long term performance of hot-poured sealant. A sealant performance ranking system was proposed based on the tests of nine sealants. The indicators of current performance evaluation, installation performance as well as thermal and immersion stability were weighted in this system. Different test results were classified and scored and then nine sealants were ranked quantitatively. The proposed system provides a more comprehensive evaluation of field performance of hot-poured sealant compared to existing performance evaluation methods, and correctly ranks the sealants in terms of their practical performance. Therefore, the proposed tests can be employed to complement current performance evaluation indicators.